Dextromethorphan: A double-edged drug - Unveiling the pernicious repercussions of Abuse and forensic implications - Lovlish Gupta; Neha Tomar; Rajendra Kumar Sarin (Elsevier, 2024)
Drug Abuse is a global menace. This problem becomes grave concern when pharmaceutical preparations are abused. Dextromethorphan (DXM) is one such drug which is an antitussive agent which is reported to be used for illicit purposes. DXM (C18H25NO) belongs to class of dissociative hallucinogens that are known to manifest detachment in sight and sound perceptions. Researchers in forensic lab in India have reported the presence of DXM in substantial amount in heroine samples as bulking agent/ additives. The drug not only adds to the bulk but also intensify the effects of heroin by synergism. Hence, it becomes mandatory that extensive studies should be carried out on every additive/ Bulking agent that is present in the seized samples so as to identify and address the abuse and trade of such compounds. The present paper aims to comprehensively study and present the Chemical Properties of the DXM and its metabolites, their pharmacological and pharmacokinetics action on Human body and other related aspects. The Compound annual growth rate, market trends, abuse trends, side effects and Forensic analysis of the Samples have been methodically presented.